The conformable condition for Nanodiscs - Cruz, Mariana M. F. da; Figueiredo, Celina M. H. de; Sasaki, Diana; Costa, Marcus T. (Anais do Encontro de Teoria da Computação (ETC); 2022: Anais do VII Encontro de Teoria da ComputaçãoDO - 10.5753/etc.2022.222595, 2022)
We investigate the total coloring of fullerene nanodiscs, a subclass of cubic planar graphs with girth 5 arising in Chemistry, motivated by a conjecture about the nonexistence of a Type 2 cubic graph of girth at least 5. We give a combinatorial description and then a conformable coloring for an infinite family of fullerene nanodiscs.